Anti‐VEGF antibody enhances the antitumor effect of CD40. Issue 8 (14th March 2014) - Selvaraj, Sathishkumar; Raundhal, Mahesh; Patidar, Ashok; Saha, Bhaskar
<x xml:space="preserve">Abstract</x> As its central immunomodulatory effects, CD40 induces interleukin (IL)‐12‐dependent antitumor immune responses; as its local protumor effects, CD40 induces the expression of vascular endothelial growth factor (VEGF) that promotes tumor angiogenesis and growth. Therefore, using a previously established tumor model in mouse, we examined if the antitumor functions of CD40 are self‐limited by VEGF induction. We observed that as the tumor mass grew during day 6 to day 18, VEGF expression in the tumor peaked with concomitant decrease in expressions of CD40 and IL‐12 but not of IL‐10. Among the angiogenic factors, VEGF‐B, VEGFR‐1, VEGFR‐2, angiopoietin‐1 and Tie2 expressions decreased, whereas the expressions of angiopoietin‐2 and angiopoietin‐3 increased with tumor growth. As significant changes in the expressions of these factors were observed on day 6, we treated the tumor‐bearing mice with the agonistic anti‐CD40 antibody or neutralizing anti‐VEGF antibody—alone or in combination—from the fifth day after the injection of tumor cells. The anti‐VEGF antibody significantly enhanced the antitumor effects of the anti‐CD40 antibody, as observed through increased survival of the mice, accompanied by reduced angiogenesis and angiopoietin‐2 expression but higher T‐cell proliferation in response to tumor antigens, increased interferon‐γ production and tumor cell cytotoxicity and higher levels of tumor antigen‐specific serum IgM, IgG1 and IgG2a, indicating B‐cell activation. Thus, our data show for the first time that the combined treatment with an agonistic anti‐CD40 antibody and a neutralizing anti‐VEGF antibody, which increases antitumor immune response or reduces local angiogenesis, respectively, is a novel antitumor strategy.